Combining ability for grain yield and other agronomic traits of early tropical maize lines under optimal, drought, and suboptimal soil nitrogen conditions - Banhoro, Abdoulazize; Nana, Rasmata; Beyene, Yoseph; Aleri, Isaiah; Chavangi, Andrew; Sory, Aboubacar; Heijde, Marc (Open Science Publishers LLP Inc., 2025)
Maize (Zea mays L.) is crucial for food security and industrial use in Sub-Saharan Africa. However, its production is limited by drought and low soil nitrogen. Therefore, developing stress-tolerant maize hybrids is essential for enhancing productivity in the region. Effective selection of these hybrids depends on understanding the mode of inheritance of new maize lines under stress conditions. The objectives of this study were thus to assess the general combining ability (GCA) and specific combining ability (SCA) effects of new maize lines under optimal, drought, and suboptimal soil nitrogen conditions. A total of 320 testcrosses, 32 lines, and 10 testers were evaluated under these conditions. Significant differences (P ≤ 0.05) were found between lines, testers, and line-by-tester interactions for most traits. Seven lines (L2, L6, L10, L18, L20, L25, and L31) and four testers (T2, T5, T9, and T10) had positive GCA effects for yield across the three growing conditions, highlighting favorable additive genetic effects under stress conditions. In addition, specific crosses including L1 × T2 and L5 × T3 (optimal conditions) and L9 × T9 and L32 × T6 (suboptimal soil nitrogen) showed positive SCA effects for yield. These lines and testers with positive GCA and SCA represent valuable genetic resources for the development of high-yielding, drought and suboptimal soil nitrogen-tolerant maize varieties.